Chlorin e6-loaded sonosensitive magnetic nanoliposomes conjugated with the magnetic field for enhancing anti-tumor effect of sonodynamic therapy. (25th November 2020) - Zhu, Hai-mei; He, Yi; Huang, Su-su; Tian, Jin-jie; Wang, Li-sheng; Hao, Jian-dong; Xie, Bo; Ling, Jia-jun
Abstract: In sonodynamic therapy (SDT), when Chlorin e6 (Ce6) accumulates in tumor tissues, its anti-tumor effect can be achieved by ultrasound activation. To increase the local drug concentration of Ce6 in tumor cells, we had established a novel drug delivery system, Ce6-loaded sonosensitive magnetic nanoliposome (Ce6/SML), which realized the targeting delivery by the external magnetic field. It was worth mentioning that the targeting release of Ce6/SML and the activation on Ce6 could be achieved simultaneously by ultrasound of SDT. In our study, after Ce6 was loaded into the sonosensitive magnetic nanoliposome (SML), the values of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in vitro and in vivo were determined, indicating the activation on Ce6 of ultrasound. The delivery system also displayed the tumor-targeting ability and anti-tumor activity, which associated with the determined tumor growth and expression levels of angiogenin (ANG), vascular endothelial growth factor (VEGF) and tumor necrosis factor-alpha (TNF-α). In conclusion, the Ce6/SML-SDT-Targeted delivery system could effectively enhance the anti-tumor activity of SDT and had a great potential application for the treatment of malignant tumors located in deep tissues.